Line parameters for hot methane ν3 band broadened by H2 from 296 to 1100 K. (March 2021) - Yousefi, Mahdi; Bernath, Peter F; Dulick, Mike; Birk, Manfred; Wagner, Georg
Highlights: High-temperature methane in planetary atmospheres. Pressure broadening and shifts of methane lines in the V 3 band. Temperature dependence of broadening and shift coefficients. Abstract: Methane (CH 4 ) spectra in the ν 3 band near 3.3 m were measured for 0, 50, 150, 240, 320, and 400 Torr pressure of added hydrogen. The spectra were recorded using a high resolution Fourier transform spectrometer. The CH 4 spectra were measured at 5 different temperatures from room temperature up to ∼ 1100 K. A multi-spectrum non-linear least squares fit method was used to determine the line parameters at each temperature. Voigt lineshape functions were used to determine the broadening and shifting of methane lines in the P and R branches. The temperature dependence of exponent parameters for the line width and the linear frequency shift coefficients were determined from a fit for temperatures ranging from 296 to 1098 K. The temperature dependence of the retrieved line broadening parameters was observed to follow the Double Power Law (DPL) proposed by Gamache and Vispoel. The temperature dependence of the pressure shift coefficients follows a linear trend for the first three temperatures. The pressure broadening parameters decrease with increasing temperature, and the pressure shift parameters increase with increasing temperature, especially for the first three temperatures. Finally, the dependence of pressure broadening ( γ 0 ) and shift ( δ 0 ) parameters on the rotational quantum number ( J ) was studied. The pressure broadening coefficients decrease about 20–30% for temperatures up to 894 K and about 40% for 1098 K, with increasing J quantum number. A complete set of fitted parameters including line position ( σ ), line intensity ( S ), pressure broadening ( γ 0 ), shifting ( δ 0 ), and their corresponding fitting errors are provided in supplementary tables.